2022
DOI: 10.5812/jjcdc.122098
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive-Behavioral Stress Management for Depression, Anxiety, Cognitive Emotion Regulation, and Quality of Life in Patients with Irritable Bowel Syndrome: A Quasi-experimental Study

Abstract: Background: Irritable bowel syndrome (IBS) symptoms increase with aggravating psychological factors such as anxiety, mood disorders, depression, and stress caused by nerve stimulation. Effective psychotherapy-based interventions are essential for medical conditions and chronic diseases. Objectives: The present study aimed to investigate the effectiveness of cognitive-behavioral stress management (CBSM) for depression, anxiety, cognitive emotion regulation (CER), and quality of life (QoL) in IBS patients. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This highlights the importance of addressing these psychosocial factors in the treatment of IBS. Specifically, interventions that target stress reduction, anxiety management, and depression may be effective in reducing cognitive distortions and improving quality of Life in IBS patients (Hofmann & Gómez, 2017;Jafari et al, 2022) Our findings also highlight the importance of addressing psychosocial factors and cognitive distortions in the treatment of IBS. Cognitive-behavioral therapy (CBT) has been shown to be an effective treatment approach for IBS, with a focus on reducing stress, anxiety, and depression, and challenging cognitive distortions (Li et al, 2014;Mahvi-Shirazi et al, 2012) Furthermore, interventions that target cognitive biases and distortions may also improve psychological and physical health outcomes in IBS patients (Hunt, 2022;Van Beugen et al, 2014) The present study highlights the importance of addressing psychosocial factors and cognitive distortions in the treatment of IBS.…”
Section: Discussionmentioning
confidence: 71%
“…This highlights the importance of addressing these psychosocial factors in the treatment of IBS. Specifically, interventions that target stress reduction, anxiety management, and depression may be effective in reducing cognitive distortions and improving quality of Life in IBS patients (Hofmann & Gómez, 2017;Jafari et al, 2022) Our findings also highlight the importance of addressing psychosocial factors and cognitive distortions in the treatment of IBS. Cognitive-behavioral therapy (CBT) has been shown to be an effective treatment approach for IBS, with a focus on reducing stress, anxiety, and depression, and challenging cognitive distortions (Li et al, 2014;Mahvi-Shirazi et al, 2012) Furthermore, interventions that target cognitive biases and distortions may also improve psychological and physical health outcomes in IBS patients (Hunt, 2022;Van Beugen et al, 2014) The present study highlights the importance of addressing psychosocial factors and cognitive distortions in the treatment of IBS.…”
Section: Discussionmentioning
confidence: 71%
“…For instance, a patient who experiences physical feelings as threats or traumas (i.e., high anxiety sensitivity) will give a response (9). As the anxiety level increases when a patient experiences such feelings, anxietyrelated problems often emerge (10). People with high anxiety sensitivity encounter stressful situations excessively through their feelings and thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive-behavioral avoidance, another common problem faced by bipolar patients (9), is a defective cognitive, affective, and behavioral system that reinforces the underlying factors of worry and stress and sets the stage for the initiation, exacerbation, and continuation of anxiety disorders (9,10). Mesri et al (11) reported that cognitive avoidance entails different strategies, such as distraction, worry, and thought suppression, that patients with panic disorder and agoraphobia adopt to avoid facing negative thoughts and unwanted problems.…”
Section: Introductionmentioning
confidence: 99%